1984
DOI: 10.1177/002221948401700705
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Linguistic Strategies in Children with Reading Disabilities in an Oral Storytelling Test

Abstract: Three groups of children: 18 dyslexic children; 18 children with reading retardation: 18 normal children (mean age -9 years), were given an oral storytelling test. The results point out a clear-cut differentiation between the three groups in their overall performance and the presence of atypical linguistic strategies in dyslexic children. The data are discussed in relation to linguistic difficulties in dyslexic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…These findings are consistent with studies of children with reading disorders whose narratives are characterized by the use of simplistic and repetitive syntactic structures, decreased lexical diversity, nonspecific pronoun use, and fewer action units (Feagans & Short, 1984; Levi et al, 1984). Although the narratives of children with SSD+LI did not differ in microstructure from the narratives of children with SSD-only at early childhood, microstructure did predict nonword reading at school age.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are consistent with studies of children with reading disorders whose narratives are characterized by the use of simplistic and repetitive syntactic structures, decreased lexical diversity, nonspecific pronoun use, and fewer action units (Feagans & Short, 1984; Levi et al, 1984). Although the narratives of children with SSD+LI did not differ in microstructure from the narratives of children with SSD-only at early childhood, microstructure did predict nonword reading at school age.…”
Section: Discussionsupporting
confidence: 89%
“…Feagans and Short (1984), for example, found that 6- and 7-year-old children with reading disability were more likely to produce fewer action units, fewer complex sentences, fewer words, and more nonreferential pronouns in their paraphrased narratives than TD children. Children with dyslexia demonstrated difficulty with the deep narrative structure in a narrative retell study by Levi, Musatti, Piredda, and Sechi (1984).…”
Section: Narratives and Literacy Developmentmentioning
confidence: 99%
“…Children with dyslexia seem to have problems-not necessarily in constructing sentences, but rather in connecting sentences using conjunctions. When asked to recall stories, they tend to omit causal and temporal links (Liles, 1985;Roth & Spekman, 1986;Weaver & Dickinson, 1982) and to provide fewer of the important details of stories that are likely to be tested in schools (Graybeal, 1981;Griffith, Ripich, & Dastoli, 1986;Hansen, 1978;Johnston, 1982;Levi, Musatti, Piredda, & Sechi, 1984;Roth & Spekman, 1986;Weaver & Dickinson, 1982). In general, oral narrative performance predicts literacy achievement (Feagans, 1982;Michaels, 1981).…”
Section: Links Between Preschool Narration and Literacy Acquisitionmentioning
confidence: 99%
“…Specifically, children who are accustomed to disambiguating pronouns in oral narratives by means of prosody are considered to produce ambiguous, poorly written narratives (Michaels & Collins 1984). Furthermore, on story-recall tasks, poor readers omit connectives between sentences (Liles 1985;Weaver & Dickinson 1982) and provide fewer of the important details of the story that are likely to be tested for in schools (Graybeal 1981;Griffith, Ripich, & Dastoli 1986;Hansen 1978;Johnston 1982;Levi, Musatti, Piredda, & Sechi 1984;Roth 1986;Weaver & Dickinson 1982).…”
mentioning
confidence: 99%